(untitled) (International Journal of Engineering and Computer Science, 2013)
All kinds of tunneling diodes make use of the quantum mechanical tunneling. A resonant-tunneling diode (RTD) is a diode with a resonant-tunneling structure in which electrons can tunnel through some resonant states at certain energy levels. In this research article, analytic model of resonant tunnelling diode (RTD) is simulated for two different structures, i.e. single barrier (1B) RTD and double barrier (2B) RTD. Different parameters such as conduction band, VI characteristics, resonant energy and transmission coefficients are studied to evaluate the performance of these structures. Double barrier RTD shows improved results in comparison to the single barrier RTD by keeping other parameters constants in absence of electric field